Complete resolution of cutaneous larva migrans with topical ivermectin: A case report. Issue 3 (7th February 2019) - Magri, Francesca; Chello, Camilla; Pranteda, Giulia; Pranteda, Guglielmo
Abstract: Cutaneous larva migrans (CLM; also called creeping eruption) is a cutaneous ectoparasitosis commonly observed in tropical countries. It is characterized by an erythematous, pruritic, and raised lesion with linear or serpiginous distribution, typically localized at the lower extremities. Oral ivermectin represents the most recommended current treatment, with important adverse effects associated. We report the clinical case of a 52‐year old with CLM, successfully treated with topical ivermectin.